2013
DOI: 10.1159/000342887
|View full text |Cite
|
Sign up to set email alerts
|

Brain Natriuretic Peptide as a Predictor of Cardioembolism in Acute Ischemic Stroke Patients: Brain Natriuretic Peptide Stroke Prospective Study

Abstract: Background and Purpose: Our previous retrospective study demonstrated that a brain natriuretic peptide (BNP) level of >140 pg/ml on admission was useful to distinguish cardioembolism (CE) from non-CE. The aim of the present study was to prospectively investigate the utility of this predefined threshold. Method: Two hundred and twenty-one consecutive patients were prospectively enrolled. On admission, the BNP levels of the patients were measured and classified according to low BNP (≤140.0 pg/ml) or high BNP (>1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 34 publications
(24 reference statements)
1
21
0
Order By: Relevance
“…Previous studies have shown that the BNP level is related to cardiac function, and it has been used as a biochemical marker of congestive heart failure. BNP levels have also been shown to be elevated in patients with acute ischemic stroke [2,3,4,5,6], in particular, those with atrial fibrillation [2,3,4,6], and associated with neurological severity [3,4,5]. Furthermore, we demonstrated that high BNP level is associated with in-hospital mortality [5] or long-term mortality [2] after ischemic stroke.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Previous studies have shown that the BNP level is related to cardiac function, and it has been used as a biochemical marker of congestive heart failure. BNP levels have also been shown to be elevated in patients with acute ischemic stroke [2,3,4,5,6], in particular, those with atrial fibrillation [2,3,4,6], and associated with neurological severity [3,4,5]. Furthermore, we demonstrated that high BNP level is associated with in-hospital mortality [5] or long-term mortality [2] after ischemic stroke.…”
mentioning
confidence: 76%
“…Recently, a rapid (approx. 15 min) and easy assay for the measurement of BNP was developed [6]. Therefore, we propose regular BNP measurements because BNP level in ischemic stroke patients provides diagnostic or prognostic information which adds to clinical variables and helps guide patient management.…”
mentioning
confidence: 99%
“…Plasma BNP concentration has been widely used as a biochemical marker of heart failure [13]. Concerning BNP and CE stroke, studies have indicated that CE stroke was predicted with AF and plasma BNP levels [14], specifically the levels on the day of admission [15]. Shibazaki et al [16] suggested that the plasma level of BNP was elevated in the acute stroke phase because heart failure may be associated with the onset of ischemic stroke in patients with AF.…”
Section: Discussionmentioning
confidence: 99%
“…Also, plasma BNP level has been shown to be an independent predictor of the mortality and myocardial infarction in stroke patients. [2345] We also notice that a few studies were accomplished in the emergency department (ED) setting and wish to make some points about our experience.…”
mentioning
confidence: 99%
“…The common target is to recognize the patients with cardioembolic stroke as soon as possible, due to high risks and poor long-term outcome, including death. [234567] Based on a lot of published studies, the BNP testing at bedside on admission, could be suggested to add into early stroke management guidelines as a strategy for improving stroke subtype classification, predict the development of atrial fibrillation after admission, and risk stratification. Thus, rapidly guiding other diagnostic tests and accelerating the start of optimal secondary prevention (e.g., control of risk factors, interventional approaches for atherosclerotic disease, antithrombotic treatments for cardioembolism, and the use of antiplatelet agents for noncardioembolic stroke), further diagnostic examination, intensive rehabilitative intervention, and ultimately better patient outcomes.…”
mentioning
confidence: 99%